CORPORATE GOVERNANCE IN SUSTAINING WAQF FUNDS: CASE STUDY IN PAHANG ISLAMIC RELIGIOUS AND MALAY CUSTOMS COUNCIL (MUIP) - Bakar, Marina Abu; Ahmad, Shofian; Salleh, Ahmad Dahlan; Salleh, Mohd Fairuz Md (International Journal of Psychosocial Rehabilitation, 2020)
Waqf is any property that a waqf giver holds on the property from any deal of sale, inheritance, grants and will while maintaining its physical resources in carrying out the welfare aimed at drawing closer to Allah. The Pahang Islamic Religious and Malay Customs Council (MUIP) were established in 1926. MUIP is committed to ensure that corporate governance practices are consistent with the applied standards of practice in Malaysia as well as ensuring the application of best practices in the organization of its investment companies. Council Members believe that good corporate governance values can help MUIP achieve its stated goals and objectives, while protecting and safeguarding the interests of stakeholders. This study was a qualitative study in the form of case study and was conducted to analyze the corporate governance practiced by MUIP in sustaining waqf funds. Data collection involved MUIP documents and semi-structural interviews with MUIP officers. Data analyses used are document and content analysis methods. The findings showed that MUIP is committed to administer waqf in Pahang state and accumulated waqf funds can be sustained as it is used for Muslim socio- economic development in Pahang state. The implication of this study is that Pahang Islamic Religious and Malay Customs Council (MUIP) is able to identify strategies that can be considered in preserving the sustainability of waqf funds in Pahang. One of the strategies used by MUIP is to combine the governance of waqf, baitulmal and investment under one administration. This has led MUIP to be able to address the issue of insufficient funds in sustaining waqf in Pahang. In addition to this, the waqf development projects that conceptualize the integration of zakat, waqf and baitulmal can help to assist development on the undeveloped waqf lands without having to wait for sufficient cash waqf contribution. The results of this study are expected to assist parties involved in managing sustainable waqf funds in the future.